Enhancing nursing students’ patient-centeredness attitudes and emotional skills through co-teaching with patients and caregivers: A mixed-methods study - Sara Alberti; Matías Eduardo Díaz Crescitelli; Loris Bonetti; Sergio Rovesti; Paola Ferri (PLoS ONE, 2025)
The objective of this study is to evaluate changes in patient-centeredness attitudes, empathy, and emotional intelligence among nursing students trained with patients and caregivers as co-teachers. A mixed-methods embedded study was conducted. The quantitative strand consists of a quasi-experimental design, measuring third-year nursing students’ scores before and after an educational intervention, compared with first- and second-year students’ scores. Data were collected using three validated scales: the Patient-Practitioner Orientation Scale (PPOS-8-IT), Jefferson Scale of Empathy Health Professions Student (JSEHPS), and Self-Report Emotional Intelligence Test (SREIT). The qualitative strand explored student perceptions through focus group post-intervention. Quantitative and qualitative data were initially analyzed separately, then triangulated during interpretation. Results showed statistically significant improvements in scale scores post-intervention (n = 146). Three themes emerged from the qualitative analysis, aligning with quantitative findings. Patient-centeredness attitudes among students increased significantly after the intervention (PPOS-8-IT mean difference = 0.26, p < 0.001). Mixed-methods analyses highlight the importance of a participatory approach to decision-making and sharing clinical information. Empathy (JSEHPS mean difference = 6.39, p < 0.001) and emotional intelligent (SREIT mean difference = 3.19, p < 0.001) also increased post-intervention. Understanding patients’ emotional states and managing one’s own emotions are integral to patient-centered practice, emphasizing the need for healthcare professionals to balance empathy with professional boundaries. Interestingly, our study found that outcomes increase over the three years of the course (n = 424). The analyses reveal that the difference among the three years is statistically significant both for the patient-centeredness attitudes (PPOS-8-IT H(2)=55.99, p < 0.001) and empathy (JSEHPS H(2)=37.78, p < 0.001).